Hydrogen Storage: Thermodynamic Analysis of Alkyl-Quinolines and Alkyl-Pyridines as Potential Liquid Organic Hydrogen Carriers (LOHC) - Sergey P. Verevkin; Sergey P. Safronov; Artemiy A. Samarov; Sergey V. Vostrikov (Applied Sciences, 2021)
The liquid organic hydrogen carriers (LOHC) are aromatic molecules, which can be considered as an attractive option for the storage and transport of hydrogen. A considerable amount of hydrogen up to 7–8% wt. can be loaded and unloaded with a reversible chemical reaction. Substituted quinolines and pyridines are available from petroleum, coal processing, and wood preservation, or they can be synthesized from aniline. Quinolines and pyridines can be considered as potential LOHC systems, provided they have favorable thermodynamic properties, which were the focus of this current study. The absolute vapor pressures of methyl-quinolines were measured using the transpiration method. The standard molar enthalpies of vaporization of alkyl-substituted quinolines and pyridines were derived from the vapor pressure temperature dependencies. Thermodynamic data on vaporization and formation enthalpies available in the literature were collected, evaluated, and combined with our own experimental results. The theoretical standard molar gas-phase enthalpies of formation of quinolines and pyridines, calculated using the quantum-chemical G4 methods, agreed well with the evaluated experimental data. Reliable standard molar enthalpies of formation in the liquid phase were derived by combining high-level quantum chemistry values of gas-phase enthalpies of formation with experimentally determined enthalpies of vaporization. The liquid-phase hydrogenation/dehydrogenation reaction enthalpies of alkyl-substituted pyridines and quinolines were calculated and compared with the data for other potential liquid organic hydrogen carriers. The comparatively low enthalpies of reaction make these heteroaromatics a seminal LOHC system.